2017
DOI: 10.5194/se-8-943-2017
|View full text |Cite
|
Sign up to set email alerts
|

Strain field evolution at the ductile-to-brittle transition: a case study on ice

Abstract: Abstract. This paper presents, for the first time, the evolution of the local heterogeneous strain field around intra-granular cracking in polycrystalline ice, at the onset of tertiary creep. Owing to the high homologous temperature conditions and relatively low compressive stress applied, stress concentration at the crack tips is relaxed by plastic mechanisms associated with dynamic recrystallization. Strain field evolution followed by digital image correlation (DIC) directly shows the redistribution of strai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…The interaction between the moving dislocations and the new grain boundaries probably contributed to the development of these defects. Deformation experiments combining high-resolution digital image correlation and EBSD in metals (Harte et al, 2020) or ice (Chauve et al, 2017b) have shown evidence for a local increase in lattice distortion (misorientation) on a scale of few micrometres from grain boundaries. Post-mortem studies using high angular resolution EBSD (Guo et al, 2014;Larrouy et al, 2015) and in situ deformation TEM experiments (Kondo et al, 2016) showed that when there is poor alignment between the slip system of the incoming dislocation and the easy slip systems in the adjacent grain, grain boundaries block the slip transfer either partially or completely, producing dislocation pile-ups and stress concentrations.…”
Section: From Subgrain (Labs) To Grain Boundaries (Hagbs)mentioning
confidence: 99%
“…The interaction between the moving dislocations and the new grain boundaries probably contributed to the development of these defects. Deformation experiments combining high-resolution digital image correlation and EBSD in metals (Harte et al, 2020) or ice (Chauve et al, 2017b) have shown evidence for a local increase in lattice distortion (misorientation) on a scale of few micrometres from grain boundaries. Post-mortem studies using high angular resolution EBSD (Guo et al, 2014;Larrouy et al, 2015) and in situ deformation TEM experiments (Kondo et al, 2016) showed that when there is poor alignment between the slip system of the incoming dislocation and the easy slip systems in the adjacent grain, grain boundaries block the slip transfer either partially or completely, producing dislocation pile-ups and stress concentrations.…”
Section: From Subgrain (Labs) To Grain Boundaries (Hagbs)mentioning
confidence: 99%
“…Indeed, recent experimental observations have (i) clearly documented the role of the crystal viscoplastic anisotropy in generating local stresses and strains markedly different from the macroscopic ones [3,32,66] and (ii) revealed that the formation of new orientations (nucleation) during dynamic recrystallization occurs through bulging (heterogeneous grain boundary migra- tion) and polygonization (formation of new grains boundaries by organization of dislocations within a grain) [3,33,63,66,73]. These two processes are controlled by the local strain and stress fields and result in recrystallized orientations that are strongly related to, but slightly different from, the parent grain orientations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, microcracking is also expected to have occurred in Qi et al 2017 [30] experiments. Strong stress concentration occurs at crack tips, and Chauve et al 2017 [73] have recently shown that, for ice, this stress concentration can be released through DRX. The R 3 iCe formulation does not account for microcracking or the effect of confining pressure.…”
Section: Discussionmentioning
confidence: 99%
“…DIC imaging of uniaxial compression creep tests in columnar ice at -7 and -10°C, 0.5 MPa to higher bulk strains showed that nucleation occurred mainly at triple junctions and along boundaries between grains with markedly different orientations, highlighting a relation between local strain incompatibility and dynamic recrystallization (Chauve et al, 2015;Piazolo et al, 2015). Grain-scale strain incompatibility also played an essential role in strain localisation at the brittle-plastic transition, where dynamic recrystallization and fracturing are coupled (Chauve et al, 2017b).…”
Section: Introductionmentioning
confidence: 96%